Predatory and competitive interaction in Anopheles gambiae sensu lato larval breeding habitats in selected villages of central Uganda - Onen, Hudson; Odong, Robinson; Chemurot, Moses; Tripet, Frédéric; Kayondo, Jonathan K. (Parasites & vectors, 2021)
Malaria is often persistent in communities surrounded by mosquito breeding habitats. Anopheles gambiae sensu lato exploit a variety of aquatic habitats, but the biotic determinants of its preferences are poorly understood. This study aimed to identify and quantify macroinvertebrates in different habitat types with determined water physico-chemical parameters to establish those preferred by An. gambiae s.l. larvae as well as their predators and competitors. Methods: A field survey was conducted in Kibuye and Kayonjo villages located in the vicinity of the River Sezibwa, north-eastern Uganda to identify Anopheline larval habitats shared by aquatic insects. Habitats were geo-recorded and as streams, ponds, temporary pools and roadside ditches. From October to December 2017, random microhabitats/ quadrats were selected from each habitat type, their water physico-chemical parameters (electrical conductivity, total dissolved solids, temperature and pH) were measured, and they were sampled for macroinvertebrates using standard dippers. All collected arthropod macroinvertebrates were then morphologically identified to family level and enumerated. Results: Principal component analysis showed that the four larval habitat types were characterized by distinct physico-chemical parameter profiles. Ponds and streams had the highest number and diversity of macroinvertebrate insect taxa and sustained few An. gambiae s.l. larvae. Anopheles gambiae s.l. were more common in roadside ditches and particularly abundant in temporary pools which it commonly shared with Dytiscidae (predaceous diving beetles) and Culex spp. Cluster correlation analysis conducted on the abundance of these taxa within quadrats suggested that An. gambiae s.l. and Dytiscidae have the most similar patterns of microhabitat use, followed by Cybaeidae (water spiders). Whilst Culex spp. co-occurred with An. gambiae s.l. in some habitats, there was only partial niche overlap and no clear evidence of competition between the two mosquito taxa. Conclusions: Ponds and streams are habitats that host the largest diversity and abundance of aquatic insect taxa. Anopheles gambiae s.l. larvae distinctively preferred temporary pools and roadside ditches, where they were exposed
Keywords: Anopheles gambiae; Malaria; larval breeding